Rubber Pad Sheet Metal Forming of Round Metal Blanks into Multi Shape Axisymmetric Cups by FEA and Experimental Methods - Karem Younis; Adnan Mohammed; Jalil Shukur (Engineering and Technology Journal, 2019)
Rubber-pad forming process of round sheet blanks into axisymmetric cups is studied by numerical and experimental approaches. In the experiments, round metal sheets are formed into the axisymmetric cups by pressing them between a rubber pad and a former block with desirable shape. To investigate influences of different parameters on the forming load, three former blocks with different shapes, blank material of low carbon steel (ST12) with thickness 0.5 mm ,three polyurethane rubber with different hardness (50,60 and 70) shore A and rubber pad having three different thickness (40,60 and 80) mm . ANSYS Workbench utilized to perform the numerical part of this research. The results showed that the produced cup height is significantly affected by rubber pad hardness.